Using Protein Motion to Read, Write, and Erase Ubiquitin Signals - Phillips, Aaron H. (J Biol Chem, 2015)
Eukaryotes use a tiny protein called ubiquitin to send a variety of signals, most often by post-translationally attaching ubiquitins to substrate proteins and to each other, thereby forming polyubiquitin chains. A combination of biophysical, biochemical, and biological studies has shown that complex macromolecular dynamics are central to many aspects of ubiquitin signaling. This review focuses on how equilibrium fluctuations and coordinated motions of ubiquitin itself, the ubiquitin conjugation machinery, and deubiquitinating enzymes enable activity and regulation on many levels, with implications for how such a tiny protein can send so many signals.